The role of industry 4.0 in sustainable supply chain: Evidence from the textile industry - Petcharaporn Chatchawanchanchanakij; Kittisak Jermsittiparsert; Thitinan Chankoson; Phutthiwat Waiyawuththanapoom (Uncertain Supply Chain Management, 2022)
The objective of this study was to examine the role of Industry 4.0 in the sustainable supply chain (SSC). The relationship between Industry 4.0, data storage, data assessment, performance evaluation, data inquiry and SSC were examined. To achieve the study objective, the mediation effect of data storage, data assessment, performance evaluation and data inquiry between Industry 4.0 and SSC was examined. Employees of textile companies were selected for data collection in Indonesia. Results of the study highlighted that Industry 4.0 had a significant positive effect on SSC. Better implementation of Industry 4.0 showed a positive effect on SSC. In addition to this, Industry 4.0 had a positive effect on data storage, data assessment, performance evaluation and data inquiry. Finally, data storage, data assessment, performance evaluation and data inquiry had a positive effect on SSC.
Keywords: Digital Transformation in Industry